68Ga-DOTATATE Uptake in an Intraosseous Hemangioma, as a Potential Cause of False-Positive PET/CT Finding, Simulating Tumoral Involvement. (13th March 2022) - Saidi, Bahare; Fallahi, Babak; Manafi-Farid, Reyhaneh; Fard-Esfahani, Armaghan; Eftekhari, Mohammad
Abstract: We present the case of a 32-year-old man with a history of hypophosphatemia and multiple bone fractures, being evaluated at our center for a potential mesenchymal tumor. 68 Ga-DOTATATE PET/CT revealed a highly 68 Ga-DOTATATE–avid lesion in the ethmoidal sinus extending to the nasal cavity. Following resection, histologic examination of the specimen confirmed the diagnosis of "intraosseous hemangioma, " a potential cause of false-positive finding of 68 Ga-DOTATATE PET/CT imaging in patients being evaluated for occult malignancies, especially at the traumatic/fractured sites.